Three promising morphological variants in clove (Syzygium aromaticum (L.) Merr. & Perry) from Tamil Nadu, India - REMA, B KRISHNAMOORTHY, J (Journal of Spices and Aromatic Crops, 1994)
Clove (Syzygium aromatieum (L.) Merr. & Perry) (Myrtaceae) plantations are limited to parts of Kerala and Kanyakumari, Tirunelveli and Nilgiris districts of Tamil Nadu in India. The plantations have originated from a few seedlings introduced from Mauritius. The oldest clove plantation in India is in Ashamboo hills (Kanyakumari district), the southern most hills of the country. Surveys were undertaken in these hills from 1992 onwards for identification of elite clove trees and variant types. Three distinctly different morphological variants located during the surveys are reported here.